2016
DOI: 10.1021/jacs.6b04833
|View full text |Cite
|
Sign up to set email alerts
|

Protein Adsorption and Reorganization on Nanoparticles Probed by the Coffee-Ring Effect: Application to Single Point Mutation Detection

Abstract: The coffee-ring effect denotes the accumulation of particles at the edge of an evaporating sessile drop pinned on a substrate. Because it can be detected by simple visual inspection, this ubiquitous phenomenon can be envisioned as a robust and cost-effective diagnostic tool. Toward this direction, here we systematically analyze the deposit morphology of drying drops containing polystyrene particles of different surface properties with various proteins (bovine serum albumin (BSA) and different forms of hemoglob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
92
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 56 publications
1
92
0
Order By: Relevance
“…[153][154][155][156] As nanomaterials have large surface-area-to-volume ratios, [157] the complexation with functional biomolecules, including phospholipids, proteins, and nucleic acids, through surface adsorption has become a practical strategy to construct the biomedical materials. [158][159][160][161] In this section, we focus on discussing the use of hydrophobic interactions to form complexes between inorganic nanomaterials and NAs.…”
Section: Complex Between Dna and Inorganic Nanoparticlementioning
confidence: 99%
“…[153][154][155][156] As nanomaterials have large surface-area-to-volume ratios, [157] the complexation with functional biomolecules, including phospholipids, proteins, and nucleic acids, through surface adsorption has become a practical strategy to construct the biomedical materials. [158][159][160][161] In this section, we focus on discussing the use of hydrophobic interactions to form complexes between inorganic nanomaterials and NAs.…”
Section: Complex Between Dna and Inorganic Nanoparticlementioning
confidence: 99%
“…This aspect which has been little studied 1,9-15 so far might become important with the emergence of (i) plasmonic applications requiring deposits with nanoscale resolution 16,17 and no structural defects, such as cracks; and (ii) biomedical applications linking diagnosis to the shape of a deposit obtained by drying a sample of biofluid. [18][19][20][21] The dynamic of particles self-assembly at the contact line during evaporation was studied at the local scale by Yan et al 22 . They showed that attractive DLVO interaction between polystyrene microparticles (~ 800 nm in size) and a negatively charged glass substrate leads to a low mobility of the particles in the vicinity of the substrate resulting in disordered local packing, regardless of the overall shape of the final deposit.…”
Section: Introductionmentioning
confidence: 99%
“…The CRE phenomenon has been the subject of broad investigations and scrutiny to unveil the underlying mechanisms 14,15 . Under certain conditions, when a particle-laden droplet is left to dry on a nonporous substrate, the colloidal particles transport to the three-phase contact line (TCL) resulting in a ring-like particle deposition 16,17 . Two decades ago, Deegan et al .…”
Section: Introductionmentioning
confidence: 99%